Birth satisfaction in different social contexts and the challenges of ensuring measurement validity - Alena Lochmannová; Colin R. Martin (BMC Pregnancy and Childbirth)
Abstract Background Birth satisfaction is shaped by social context, yet its assessment faces methodological challenges, particularly in marginalized populations. This study examines birth satisfaction among incarcerated and non-incarcerated women, considering both experiential disparities and potential measurement biases. Methods A nested retrospective cross-sectional study was conducted with 55 incarcerated women who had given birth prior to incarceration and 79 women from the general population in the Czech Republic. Birth satisfaction was assessed using the Birth Satisfaction Scale–Revised. All participants completed a standardized pencil-and-paper survey. Responses between incarcerated and non-incarcerated participants were compared, and pencil-and-paper responses of non-incarcerated participants were compared with survey-only administration to validate the survey method. Results Incarcerated women reported significantly higher birth satisfaction scores than those in the general population. In the prison population, higher birth satisfaction correlated positively with self-esteem and negatively with PTSD symptoms. Comparison of pen-and-paper and online survey administration in the general population revealed no significant differences, supporting confidence in the equivalence of paper and pencil data capture method in the incarcerated population. Conclusions These findings highlight the importance of context in birth satisfaction assessments, as incarcerated women’s experiences may be shaped by institutional constraints and psychological dynamics. Ensuring methodological consistency is essential for valid cross-population comparisons and the accurate interpretation of birth satisfaction data.